Nutrient management in turmeric (Curcuma longa L.) in an integrated farming system in southern Kerala - Varghese, S R Isaac, J (Journal of Spices and Aromatic Crops, 2016)
A field trial was conducted to assess the effect of different organic manures produced in situ in an integrated farming system at Farming Systems Research Station, Sadanandapuram during 2012–13 on the performance of turmeric, variety Suguna, grown as component crop in the system under nutrient recommendation of 30:30:60 kg NPK ha-1. Higher plant growth was recorded in the treatment integrating 75% recommended dose nitrogen as organic manures and remaining 25% as inorganic fertilizers. Rhizome yields were significantly highest (42.71 t ha-1) in the treatment receiving vermicompost along with chemical fertilizers followed by poultry manure substitution (33.08 t ha-1) and sole organics - integration of vermicompost enriched with PGPR Mix I with poultry manure and goat manure (31.61 t ha-1). Net returns per ha ranged between Rs. 1.82 lakh (inorganic fertilizers alone) and Rs. 5.8 lakh (vermicompost + inorganic fertilizers) and benefit cost ratios between 1.76 and 3.19.